ANALYSIS OF CONTROVERSIAL ARTICLES IN THE DRAFT CRIMINAL PROCEDURE CODE (RUU KUHAP) AND THEIR IMPLICATIONS FOR CRIMINAL LAW POLICY - Heru Karyono; Bambang Ali Kusumo (CV. RADJA PUBLIKA, 2025)
The Draft of the Indonesian Criminal Procedure Code (RUU KUHAP) is formulated as a reform of Indonesia’s criminal procedure system to align with legal developments and societal needs. However, a critical review of several key articles within the draft reveals potential issues that may affect the effectiveness of law enforcement and the protection of human rights. These issues include imbalances in investigative authority, ambiguity in the concept of restorative justice, threats to privacy rights through wiretapping, and inconsistencies between witness protection and criminal sanctions. Additionally, limitations on pretrial rights, unclear provisions regarding electronic evidence, and uncertainty in the review (judicial reconsideration) mechanism are significant concerns. Using a normative juridical approach and qualitative analysis, this article recommends the refinement of problematic articles in the draft to ensure alignment with principles of justice, legal certainty, and human rights protection, while also addressing the needs of a modern and balanced criminal justice system.